Orchestration system architecture design and implementation of smart line service - Huiguang CHEN; Huan LI (Dianxin kexue)
In the era of SDN/NFV technology, in order to meet the goal of rapid and automatic activation of new network services, a solution about the architecture and implementation of orchestrator system was introduced.According to the characteristics of loose coupling and flexible deployment of each function, the orchestrator’s system architecture was divided into service entry, network and adapter.The choreographer workflow was divided into the business preparation workflow and the business delivery workflow.Through practicing and verifying, as the core system, the smart line basically met the initial business requirements and maintenance management requirements of the business choreographer.